Implementasi Peraturan Bupati Mandailing Natal Tentang Pakaian Muslim Dan Muslimah - Padilah, Riski (Jurnal El-Thawalib, 2022)
This research examines Mandailing Natal Regent Regulation Number 16 of 2019 concerning Muslim and Muslimah Clothing for State Civil Apparatuses in Mandailing Natal District in the Siyasah Fiqh Perspective. This research is a field research with a qualitative approach, the primary data source is the Mandailing Natal Regent's office. The primary data source in this study was data obtained from the head of the legal section of the Mandailing Natal Regent's office, namely Mr. Nurkholis S.H., M.H, along with staff in the legal, population and general departments at the Mandailing Natal Regent's Office. Secondary data sources for this researcher are books, articles, and other sources related to this research. Data collection techniques in this study are Observation, Interview, and Documentation. With qualitative descriptive data analysis techniques. The results of this study are that the Implementation of Mandailing Natal Regent Regulation Number 16 of 2019 concerning Muslim and Muslimah Clothing for State Civil Apparatuses in Mandailing Natal Regency, namely that there are still many employees who have not fulfilled the values of the Regent's regulations. Obstacles in implementing Regent Regulation Number 16 of 2019, namely for male Muslim employees wearing sarongs sometimes going to the office in a hurry is not possible to wear sarongs because wearing sarongs takes quite a long time, for female Muslim employees wearing the syar'i hijab it is still said to be far from Islamic rules because it still uses thin and newfangled materials. And Review of Fiqh Siyasah on the Implementation of Mandailing Regent Regulations Concerning Muslim and Muslim Women's Clothing for State Civil Apparatuses in Mandailing Natal District. Based on the Qur'an surah An-nisa Verse 59, that is, we are ordered to obey Allah, the Messenger and also the Leader, and the sources of law and our guidance in life are the Al-Qur'an and Hadith, and what is contained in the hadith, namely a leader is not only is responsible to his people but he also has to be responsible to Allah SWT, therefore the leader must make decisions in accordance with the Al-Qur'an and hadith to achieve benefit for humans